PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY BERBANTUAN ASSEMBLR EDU PADA MATA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS V - Annisa Ulkhoiroh; Sukmawarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop Augmented Reality-based learning media assisted by Assemblr Edu to improve students' conceptual understanding in mathematics subjects. This research is a type of Research and Development (R&D) using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The study was conducted at SDN 108239 Tanjung Mulia. Research data were obtained from material and media validation, as well as from teacher response questionnaires and students' conceptual understanding tests.The results showed that the Augmented Reality-based learning media assisted by Assemblr Edu was declared feasible by two validators media and material experts. The material validation yielded a feasibility percentage of 100%, while media validation reached 83.3%. Additionally, teacher responses to the media reached 100%, falling into the "highly feasible" category. The validity test results for the students' conceptual understanding test showed that the calculated r value was greater than the table r value, and the significance value was less than 0.05. With r table at n = 24 and α = 0.05 being 0.404, the instrument was deemed valid.Based on the research findings, it can be concluded that the development of Augmented Reality-based learning media assisted by Assemblr Edu is overall feasible for use in the school learning process to improve students' conceptual understanding in mathematics.